The Association Between Maladaptive Metacognitive Beliefs and Emotional Distress in People Living With Amyotrophic Lateral Sclerosis - Dodd, Rachel; Fisher, Peter L.; Makin, Selina; Moore, Perry; Cherry, Mary Gemma (Frontiers in Psychology, 2021)
Objective: Approximately half of all people living with Amyotrophic Lateral Sclerosis (ALS) experience persistent or recurrent emotional distress, yet little is known about the psychological processes that maintain emotional distress in this population. The Self-Regulatory Executive Functioning (S-REF) model specifies that maladaptive metacognitive beliefs and processes are central to the development and maintenance of emotional distress. This study explored whether maladaptive metacognitive beliefs are associated with emotional distress after controlling for demographic factors, time since diagnosis, and current level of physical functioning. Design: In a cross-sectional design, 75 adults with a diagnosis of ALS completed self-report questionnaires. Participants had a mean age of 60.40 years, mean duration of symptoms 63.92 months, and male:female gender ratio of 14:11. Main outcome measures: Questionnaires assessed emotional distress (HADS, adapted for ALS), physical functioning (ALSFRS-R), repetitive negative thinking (RTQ-10), metacognitive beliefs (MCQ-30) and demographic factors. Results: Maladaptive metacognitive beliefs explained additional variance in emotional distress after controlling for age, gender, time since diagnosis, physical functioning and repetitive negative thinking. Repetitive negative thinking partially mediated the relationships between positive and negative metacognitive beliefs and emotional distress. Conclusions: These data support the utility of the metacognitive model in understanding emotional distress in people with ALS. Examination of the temporal relationship between maladaptive metacognitive beliefs and emotional distress in people living with ALS may help to guide the development of therapeutic approaches.